(untitled) (Global Journal of Management and Business Research, 2013)
There is an increased trend of online businesses through social networks. The power of socialmedia sites is the main reason to promote online businesses. Every business must become an online business. That is, every business needs an online presence of some kind. The purpose of our study is to find out the role of social media on online businesses, the awareness of this trend amongst people and if this trend is beneficial in the near future. A group of 210 people take part in this research through a predesigned questionnaire. According to the results of survey, there is no association between the role of social media on online businesses the percentage of awareness among people of the changing trends and gender. There is association between benefits of online business trend in the near future and gender. By this research, we came to conclusion that people are not much aware about the trend of online businesses through social media but are aware of its benefits in the near future. So, the responses are neutral.